Reliability Evaluation of 33/11kV Olunde Injection Substation for Improved Performance - Olayinka Matthew Oyeleye; Olatunde Adeyemo; Thomas Olabode Ale (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
Electric power supply reliability (PSR) is crucial in the present economy to avoid huge economic loss and life discomfort. Thus, there is need to improve PSR. Reliability evaluation of power equipment was carried out on Olunde 33/11kV Injection Substation using extracted and available five years data of Fault Frequency and Downtime of associated power equipment for 2016 to 2020 from the Injection Substation’s log books. Fault Tree Analysis (FTA) Technique was used in this research. The existing Injection Power Substation results shows that the overall injection substation unavailability of power supply was 0.00672; 33kV NBL Feeder alone has the highest percentage of failure contribution 72.97% of the unavailability of the injection substation. The reliability improvement of the Injection Power Substation using doubling maintenance activities method on the NBL 33kV feeder shows that the overall injection substation unavailability improved from 1:1.57; the NBL 33kV feeder failure contribution reduced to 15.63%. Using a redundant feeder, 33kV feeder, the overall unavailability of the injection substation improved from 1:3.6; the NBL 33kV failure contribution reduced to 1.31%. The redundant feeder approach in this work is highly significant since it is better than the doubling maintenance activities method.